Efek Nefroprotektif Bit Merah (Beta vulgaris L) terhadap Gangguan Ginjal Akibat Paparan Campuran Pestisida : Study Eksperimen pada Tikus Wistar - Kartika Ikawati; Armydha Dwi Susanti (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
One of the risk factors for kidney disorders is excessive pesticide exposure. Kidney dysfunction is characterized by an increase in urea and creatinine levels. Red beetroot (Beta vulgaris L) contains bioactive compounds that are considered capable of reducing the risk of kidney disorders caused by pesticide exposure. This study aimed to prove the nephroprotective effect of red beetroot (Beta vulgaris L) against kidney damage induced by mixed pesticide exposure through an experimental study on Wistar rats. This research used an experimental design with a post-test only randomized control group design. The study population consisted of male Wistar rats. A total of 36 rats were included as samples, with inclusion criteria of being healthy, aged 2–3 months, and weighing 150–200 g. Sampling was carried out randomly. The animal experiments were conducted at the Faculty of Mathematics and Natural Sciences, UNNES Semarang, while the examination of urea and creatinine levels was performed at the Laboratory of AKKES 17 August 1945 Semarang. Urea and creatinine levels were measured semi-automatically. Data were analyzed using ANOVA and Post Hoc tests. The results showed that pesticide exposure for 14 days significantly increased urea and creatinine levels (p = 0.000). Administration of red beetroot extract to rats exposed to pesticides significantly reduced urea and creatinine levels (p = 0.000), with the optimal dose being 400 mg/kg body weight. It can be concluded that red beetroot extract has a nephroprotective effect against kidney damage caused by mixed pesticide exposure.